First record of Xiphinema hunaniense Wang & Wu, 1992 (Dorylaimida: Longidoridae) associated with tea (Camellia sinensis (L.) Kuntze) in Thanh Hoa, Vietnam - Linh, Le Thi Mai; Tien, Nguyen Huu; Duyen, Nguyen Thi; Phap, Trinh Quang (Academia Journal of Biology, 2021)
The dagger nematodes, Xiphinema spp., are migratory root-ectoparasitic nematodes that cause damage to a wide range of wild and cultivated plants over the world. In Vietnam, this nematode group has been studied mainly based on morphological characterizations. During a survey of pathogens associated with tea, a plant with many medicinal and therapeutic potentials, a population of Xiphinema hunaniense was recorded. This study provides the first morphological and molecular characterizations of Xiphinema hunaniense found on Tea in Vietnam. The 28S rDNA, and 18S rDNA phylogenetic trees of the genus Xiphinema are also provided. 18S rDNA sequence of X. hunaniense is also submitted to GenBank for the first time.